The power of education in refugees' lives: Sri Lankan refugees in India - Mayuran, A (Refugee Studies Centre, University of Oxford, 2017)
In their determination to take control of an uncertain future, Sri Lankan refugees living in the camps of Tamil Nadu, India, have prioritised education. The story of how they did this, and the crucial role of the host government in supporting them, may inspire other refugee communities who wait in uncertainty for a durable solution.